Hybrid Bilayer WSe2–CH3NH3PbI3 Organolead Halide Perovskite as a High‐Performance Photodetector. Issue 39 (7th September 2016) - Lu, Junpeng; Carvalho, Alexandra; Liu, Hongwei; Lim, Sharon Xiaodai; Castro Neto, Antonio H.; Sow, Chorng Haur
Abstract: A high‐performance 2D photodetector based on a bilayer structure comprising a WSe2 monolayer and CH3 NH3 PbI3 organolead halide perovskite is reported. High performance is realized by modification of the WSe2 monolayer with laser healing and perovskite functionalization. After modification, the output of the device was three orders of magnitude better than the pristine device; the performance is superior to that of most of the 2D photodetectors based on transition‐metal‐dichalcogenides (TMDs). This result indicates that combinatory TMDs–halide perovskite hybrids can be promising building blocks in optoelectronics. Abstract : A high‐performance photodetector was realized by modification of a WSe2 monolayer using a laser‐healing technique and perovskite functionalization. Modification and interface engineering of transition‐metal‐dichalcogenides with halide perovskites, yields hybrid materials that may be promising building blocks in optoelectronics.